Managing Production Systems Abroad: A Note on Organizational Framework - Prasad, S. Benjamin (Academy of Management Journal, 1970)
The article presents a speech by S. Benjamin Prasad, delivered at a March 1970 meeting of the Western Division of the Academy of Management, in Salt Lake City, Nevada, in which he discusses the topic of industrial production systems.